2005
DOI: 10.1016/j.femsle.2005.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Novel target genes of PsrA transcriptional regulator ofPseudomonas aeruginosa

Abstract: The PsrA transcriptional regulator is involved in stationary phase induced transcriptional regulation of rpoS and in negative auto-regulation in Pseudomonas aeruginosa. This study was designed to determine whether other loci were regulated by PsrA in P. aeruginosa. Computer search was performed of the PsrA binding motif (G/CAAAC N(2-4) GTTTG/C) against the P. aeruginosa genome sequence. Four of 14 analysed promoters responded to and bound PsrA; (i) divergent promoters controlling PA2952/PA2951 and PA2953, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 20 publications
7
52
0
Order By: Relevance
“…Experimentally determined PsrA binding sites in the promoter regions of the PsrA-repressed genes psrA, PA0506 (acdH), and PA2952 (etfB) coincide with the predicted PsrA binding sites (20). For the rpoS gene, which is positively regulated by PsrA at the stationary phase, the experimentally determined PsrA binding site is located 411 bp upstream of its translational start point (19) and was thus missed by our procedure.…”
Section: Vol 191 2009 Comparative Genomics Of Fa and Ilv Degradatiomentioning
confidence: 63%
See 1 more Smart Citation
“…Experimentally determined PsrA binding sites in the promoter regions of the PsrA-repressed genes psrA, PA0506 (acdH), and PA2952 (etfB) coincide with the predicted PsrA binding sites (20). For the rpoS gene, which is positively regulated by PsrA at the stationary phase, the experimentally determined PsrA binding site is located 411 bp upstream of its translational start point (19) and was thus missed by our procedure.…”
Section: Vol 191 2009 Comparative Genomics Of Fa and Ilv Degradatiomentioning
confidence: 63%
“…Their representatives in P. aeruginosa were previously described as being LiuR and PsrA. In particular, the P. aeruginosa regulator PsrA from the TetR family was originally shown to be involved in the stationary-phase-induced transcriptional regulation of rpoS and some other genes (18,19,20). Here, we perform a comparative genomic reconstruction of the respective regulons in proteobacteria and report that their major targets are the ILV degradation and FAD pathways, respectively.…”
mentioning
confidence: 96%
“…The PAO1-P fadBA5 -lacZ fusion strain was used in transposon mutagenesis to identify a regulator for fadBA5, which is PsrA (PA3006). The DNA recognition sequence for PsrA binding is well established (Kojic et al, 2005;Shen et al, 2006). Downstream of the fadBA5 promoter region, there were two putative PsrA binding sites (Figs 2a and 7).…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested elsewhere that PsrA, a member of the TetR family of repressors, could affect global gene expression (Kojic et al, 2005;Shen et al, 2006), including activation of rpoS (Kojic et al, 2002) and the type III secretion system exsCEBA operon (Shen et al, 2006). A proteomic study has shown that PsrA influences the expression of a few proteins, including FadBA5, but the signal (inducer) and mechanism of regulation by PsrA have not been demonstrated (Kojic et al, 2005).…”
Section: Psra Affects Gene Expression Globallymentioning
confidence: 99%
See 1 more Smart Citation